Neurotensin promotes hepatic steatosis by regulating lipid uptake and mitochondrial adaptation in hepatocytes - Moumita Banerjee; Jun Song; Baoxiang Yan; Haoming Wu; Shaghayegh Norouzi; Tomoko Sengoku; Savita Sharma; Teresa W. M. Fan; Eun Lee; Daheng He; Chi Wang; Jinpeng Liu; et al. (Cell Death and Disease)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is a multifactorial disease characterized by hepatic steatosis. Mitochondrial dysfunction resulting in the incomplete digestion of surplus fat is one of the key factors that lead to hepatic steatosis but the reason for this remains unclear. We investigated the role of neurotensin (NTS), a gut hormone, in inducing maladaptive fat metabolism in steatotic liver. We identify CD36 and PGC1α, two critical drivers of MASLD, as direct NTS signaling targets in the liver. NTS upregulates CD36, a free fatty acid receptor, in hepatocytes and promotes long chain lipid uptake. Conversely, NTS inhibits PGC1α, which acts as a lipid sensor and translocates to the nucleus to activate lipid catabolism-related genes in an AMPK-dependent manner. Thus, a high fat diet decreases the fatty acid oxidation and oxidative phosphorylation capacity of the liver and hepatocytes from NTS or NTS receptor 1 (NTSR1) wild type mice; whereas NTS deficiency preserves the lipid metabolism capacity of the liver. NTS signaling is significantly upregulated in MASLD and in metabolic dysfunction-associated steatohepatitis (MASH) human liver samples when compared to normal livers, which correlates with the expression of CD36 and oxidative phosphorylation proteins. These findings provide critical mechanistic insights into the maladaptive fat metabolism noted with steatosis in mice and humans and suggest novel strategies for therapeutic intervention of MASLD, which affects nearly one-quarter of the global population.